ANALYSIS OF MARKETING STRATEGY IN AN EFFORT TO ATTRACT CONSUMER BUYING INTEREST ON MSME PEYEK SARI MENIR GUNUNG KIDUL - Wulan Probo Bintari; Agus Dwi Cahya; Novita Wulandari (Universitas Putera Batam, 2021)
Marketing strategy has an important role for Micro, Small and Medium Enterprises (MSMEs). The important role of the right marketing strategy will be able to attract consumers to buy the products. Currently, MSMEs in Indonesia are experiencing very rapid development, especially in the culinary field.